DESAIN DAN IMPLEMENTASI SISTEM INFORMASI ADMINISTRASI PADA CV. DIAN ABADI MALANG BERBASIS DESKTOP - Widayanti, Rahayu; Hidayat, Fahrul (DINAMIKA DOTCOM, 2013)
Administration is a very important activity for the Dian Abadi CV Malang. These activities include the preparation and recording of employee data outsoursing be used to create payroll reports, and data stationery (ATK), which will be offered to customers Dian Abadi CV Malang. Preparation and recording of data and information systematically in order provide information that is required by the owner of CV Dian Abadi Malang.This research aims to design and implement information systems to desktop-based administration. Through the use of information technology will allow administrative activities are more easily, quickly, and accurately when compared with manual work. This information system is automatically expected to make a report that will allow the owner to carry out the control and supervision of the company.Development of the system in this study using the System Development Life Cycle (SDLC). SDLC is a structured framework that contains sequential processes in which information systems are developed. Keywords: design, implementation, system, information, administration, desktop, CV. Dian Abadi Malang